Highly pathogenic avian influenza H5N1 virus could partly be evacuated by pregnant BALB/c mouse during abortion or preterm delivery - Deng Wei; Bao Linlin; Xu Lili; Qin Chuan (Virology Journal, 2011)
Abstract The highly pathogenic avian influenza H5N1 virus is one of candidates for future pandemic. Since H5N1 viruses had previously been isolated only from avian species, the outbreak raised questions about the ability of these viruses to cause severe disease and death in humans. Pregnant women are at increased risk for influenza-associated illness and death. However, little is known about whether influenza viruses could transmit to the fetus through the placenta, and the effects of abortion and preterm delivery to maternal influenza infection are not well understood. We found that the H5N1 viruses could vertical transmit to the fetus through the placenta in the BALB/c mouse model, and the viruses could partly be evacuated by the pregnant mice during abortion or preterm delivery. This study may further our understanding about the transmission of this highly pathogenic avian influenza viruses, supply optimized clinical treatment method for pregnant women, and shed some light on better preventing and controlling for future potential outbreak of H5N1 influenza pandemic.